Literature Review: Manajemen Strategis dalam Peningkatan Kinerja Layanan Karantina Hewan, Ikan, dan Tumbuhan di BKHIT Maluku - Andri Maulana Yusup; Alrino Ode Masimu; Rustam Ode Nuru; Safrina Marajabessy (SAFE-Network, 2026)
The Animal, Fish, and Plant Quarantine Center (BKHIT) Maluku plays an important role in preserving biodiversity and supporting agricultural commodity trade in Maluku Province. This article examines the implementation of strategic management at BKHIT Maluku through a systematic literature review from 2020 to 2026. Data were collected from scientific journals, policy documents, and official reports through four stages, namely identification and screening of relevant sources in academic databases; selection of materials related to strategic management in public organizations and island governance; thematic analysis to discover recurring patterns, strategies, and trends; and development of an analytical framework based on strategic management theories including Resource Based View, Stakeholder Theory, Balanced Scorecard, Dynamic Capabilities, and Public Service Motivation adapted to BKHIT Maluku's conditions. The results indicate that BKHIT Maluku faces a complex strategic situation with high biodiversity as a strength, limited budget and infrastructure as weaknesses, digital transformation programs as opportunities, and climate change as threats. The proposed strategies include digital technology utilization, human resource development through blended learning, strengthening community-based surveillance, and cross-sectoral collaboration to achieve organizational objectives and overcome archipelago governance challenges.